2017
DOI: 10.30638/eemj.2017.125
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Social Responsibility: Competitiveness in the Context of Textile and Fashion Value Chain

Abstract: In this paper we address Corporate Social Responsibility (CSR) as a competitive factor in textile and fashion value chain. CSR assumes a large range of activities focused on one or multiple targets, from work conditions to social programs, or environmental impact. The influence of CSR strategies on market performance depend on how truthful consumers will understand and believe to be the values offered by companies. The qualitative research has considered seven case studies from Portuguese textiles and fashion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Another study by J. Hsu and M. Chengalso found that cost and time to be the barrier in implementing CSR [24] . Additionally, the study by Guedes et al show that the major barrier to implement CSR for SMEs are cost and lack of human resources [23] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by J. Hsu and M. Chengalso found that cost and time to be the barrier in implementing CSR [24] . Additionally, the study by Guedes et al show that the major barrier to implement CSR for SMEs are cost and lack of human resources [23] .…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of CSR program are affected by unique factors for each unique individual CSR program according to study done by Irwanto and Prabowo [20] . While a comprehensive study on the barriers to CSR implementation is lacking [21] , there are however, some relevant studies in regard of the hindrance of implementing CSR such as the study by Thongthippa [22] , Guedes et al [23] , and J.Hsu and M.Cheng [24] .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, different studies used the multiple case study design to examine CSR strategies' drivers and barriers (Govindasamy & Suresh, 2018;Guedes et al, 2017;Koeksal & Straehle, 2021;Van & Nguyen, 2019), showing that the main drivers are the competitive context, the social influences, the managers' knowledge of CSR, the company's internal culture, as well as market promotion and building a reputation with stakeholders and the government. Additionally, the most significant obstacles were a lack of resources in expertise, information, finance, and training, as well as the cost of CSR initiatives and internal and external communication.…”
Section: Circular Economy and Corporate Social Responsibility Issues ...mentioning
confidence: 99%
“…The latter allow companies to reduce the environmental burden associated with their production activities, and at the same time to foster the development of new products, technologies, or business structures, which increases their overall market viability [38]. As demonstrated in recent studies, the implementation of Corporate Social Responsibility (CSR) strategies gained importance for the competitiveness in the textile sector [39][40][41][42]. One of the strategic CSR areas is the so-called "marketplace CSR", which includes company's communication with its suppliers, consumers, and other stakeholders along the value chain.…”
Section: Textile Ecolabelsmentioning
confidence: 99%